Analysis on the Complete Mitochondrial Genome of Andraca theae (Lepidoptera: Bombycoidea). Issue 1 (1st October 2016) - Gu, Xing-Shi; Ma, Li; Wang, Xing; Huang, Guo-Hua
Abstract: The bombycid moth, Andraca theae (Matsumura) (Lepidoptera: Bombycoidea) is an important pest of tea in southeastern China. In the present study, the mitochondrial genome (mitogenome) of A. theae was amplified by polymerase chain reaction and sequenced. The complete mitogenome of A. theae, encoding 37 genes, was 15, 737 bp in length (Genbank no. KX365419), and consisted of 13 protein-coding genes (PCGs), 22 tRNA genes, 2 ribosomal RNA genes and an adenine (A) + thymine (T)-rich region (AT-rich region). The gene order of A. theae mitogenome was typical for Lepidoptera mitogenomes. Except for cox1, which started with CGA, all other 12 PCGs started with ATN. Eleven of the 13 PCGs ended with TAA, expect for cox1 and cox2, which ended with a single T. The maximum likelihood method and the Bayesian method were used to analyze the phylogenetic relationship among 22 representative bombycoid species with a matrix consisting of the 13 PCGs of the mitogenomes of the 22 species. The topological structures of the two phylogenetic trees we constructed were almost identical, with the results indicating that the bombycid species, including A. theae, clustered into a single clade with a bootstrap value of 58% and a posterior probability of 0.98. The phylogenetic relationship among the Bombycoidea species analyzed was Lasiocampidae + (Bombycidae + (Saturniidae + Sphingidae)) which was supported by a high bootstrap value of 100% and a posterior probability of 1.00.